(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the results of transurethral resection of prostate with transvesical prostatectomy in respect to the incidence, and severity of postoperative urinary incontinence. Study Design: Comparative cross sectional study. Place and Duration of Study: This study was carried out in GMMMC Hospital Sukkur, Pakistan, where all transvesical prostatectomies were performed. It was two years study from feburvoury 2008 to March 2010. Materials and Methods:280 patients were selected, they were diveded in two groups and 140 Patients underwent TURP were kept in group A, and 140 patients transvesical prostatectomy group was titled as B. Patients having associated stricture urethra, urinary bladder stones or bladder diverticulum and later on proved a scarcinoma of prostate were excluded form the study. Results: From group-A (TURP Group) 20 (14.28%) Patients developed incontinence postoperatively and all had stress type of incontinence. While in group B Transvesical prostatectomy 37 (26.4%) patients developed urinary incontinence. 30(21.4) patients had stress incontinence and 7(5%) patients developed continuous urinary leakage. Rate of recovery after conservative measures remained rapid with group A as compared to group B. Conclusion: Frequency and severity of postoperative urinary incontinence is more with transvesical approach. But the facility of TURP is not freely available. Therefore improvement in the technique of open prostatectomy is mandatory. For which recommendations have been given.